Utilisation of community care services and self-rated health among elderly population in China: a survey-based analysis with propensity score matching method - Liu Yang; Lijian Wang; Xiaodong Di; Xiuliang Dai (BMC, 2021)
Abstract Background Elderly care and elderly health are the enormous challenges in such an aging society as China. Community care services have been developing rapidly in recent years in China as an increasingly mainstream care resource to promote elderly health. The purpose of this study is to examine the association between using community care services and self-rated health among Chinese elderly. Methods A cross-sectional survey was conducted in 2019 and 612 elderly people from China's Shaanxi province were enrolled. The binary logistic regression was first employed to explore the association between community care services utilisation and elderly health. Given the potential selection bias issue, the propensity score matching method was hired to generate comparable samples between participants who used these services and participants who didn't, and further examine the health benefits of using four types of services. Results The results of the binary logistic regression showed that the use of community care services predicted a better health status of elderly individuals. Overall, the results of the propensity score matching method showed the similar results. Specifically, with the nearest neighbors matching algorithm, using daily care services was significantly associated with a 0.246 increase in the self-rated health of the elderly (T = 1.83). For medical care services, the mean of self-rated health of elderly individuals who used these services was 3.542, significantly higher than those who didn't (T = 2.15). For spiritual comfort services, elderly individuals using these services showed a significant increase by 0.280 in the self-rated health (T = 1.82). For social and recreational services, the result of the nearest neighbor matching method was not statistically significant, while the results of kernel matching method and the mahalanobis matching method showed a significant increase in the self-rated health among elderly individuals using these services (T = 2.03, T = 2.03, respectively). All the estimated results passed the Rosenbaum bounds analysis and were not sensitive to hidden bias. Conclusions Using community care services improved the self-rated health of the elderly. More effective measures may be implemented to increase access to care resources for senior citizens, and further improve their health status.